Specific impact of cardiovascular risk factors on coronary microcirculation in patients with subclinical hypothyroidism: Coronary in subclinical hypothyroidism - Stojković, Mirjana; Nedeljković-Beleslin, Biljana; Tesic, Milorad; Bukumiric, Zoran; Ciric, Jasmina; Stojanovic, Milos Stojanovic; Miletic, Marija; Djordjevic-Dikic, Ana; Giga, Vojislav; Beleslin, Branko; Zarkovic, Milos (Journal of Medical Biochemistry, 2021)
Background: Although thyroid hormones have significant effect on cardiovascular system, the impact of subtle thyroid dysfunction such as subclinical hypothyroidism (SCH) remains to be determined. We investigated coronary flow reserve (CFR) in patients with subclinical hypothyroidism.Methods: Thirty-two subjects with SCH and eighteen control subjects with normal serum thyroid hormones and thyroid-stimulating hormone (TSH) levels were included in the study. TSH, free thyroxine, free triiodothyronine, glucose, insulin, HbA1c, cholesterol, triglyceride and plasma levels of C-reactive protein were measured. Coronary diastolic peak flow velocities in left anterior descending coronary artery were measured at baseline and after adenosine infusion. CFR was calculated as the ratio of hyperemic to baseline diastolic peak velocity.Results: CFR values were not significantly different between the two groups (SCH 2.76 ± 0.35 vs controls 2.76 ± 0.42). There was a significant correlation of CFR with waist to hip ratio, hypertension, smoking habits, markers of glucose status (glucose level, HbA1c, insulin level, HOMA IR), cholesterol, LDL-cholesterol and triglyceride levels in SCH group, whereas only cholesterol level showed significant correlation with CFR in controls. There was no correlation between CFR and thyroid hormones.Conclusion: We concluded that there is a different impact of cardiovascular risk factors on CFR in SCH patients compared to healthy control and that these two groups behave differently in the same circumstances under the same risk factors. The basis for this difference could be that the altered thyroid axis “set point” changes the sensitivity of the microvasculature in patients with SCH to known risk factors.
Keywords: cardiovascular risk factors; coronary flow reserve; subclinical hypothyroidism; thyroid